2021
DOI: 10.1248/bpb.b21-00520
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Toxic Advanced Glycation End-Products Induces Cytotoxicity and Inflammation in Hepatocyte-Like Cells Differentiated from Human Induced Pluripotent Stem Cells

Abstract: Nonalcoholic steatohepatitis (NASH), the aggressive form of the most common chronic liver disease nonalcoholic fatty liver disease, is characterized by inflammation and damage in the liver. Although hepatocyte injury and cell death have been identified as cardinal pathological features of NASH, its pathogenesis has not yet been elucidated in detail. Immortalized cell lines and primary cultured cells have been used as in vitro models of NASH. However, these cells have several disadvantages, such as specialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 13 publications
1
30
1
Order By: Relevance
“…However, they have several disadvantages, such as specialized characteristics by immortalization or limited growth potential. A decrease was noted in the viability of hepatocyte-like cells (HLCs), which differentiated from human induced pluripotent stem cells (hiPSCs) (hiPSC-HLCs), as TAGE accumulated in cells, which was consistent with previous findings on HCC cells and primary cultured hepatocytes [33]. In addition, the accumulation of TAGE up-regulated the expression of inflammationrelated genes (i.e., interleukin (IL)-6, IL-8, and monocyte chemoattractant protein (MCP)-1) in hiPSC-HLCs.…”
Section: Isupporting
confidence: 89%
See 3 more Smart Citations
“…However, they have several disadvantages, such as specialized characteristics by immortalization or limited growth potential. A decrease was noted in the viability of hepatocyte-like cells (HLCs), which differentiated from human induced pluripotent stem cells (hiPSCs) (hiPSC-HLCs), as TAGE accumulated in cells, which was consistent with previous findings on HCC cells and primary cultured hepatocytes [33]. In addition, the accumulation of TAGE up-regulated the expression of inflammationrelated genes (i.e., interleukin (IL)-6, IL-8, and monocyte chemoattractant protein (MCP)-1) in hiPSC-HLCs.…”
Section: Isupporting
confidence: 89%
“…Furthermore, we indicated the inhibition of autophagy by intracellular TAGE [ 37 ]. Although previous studies demonstrated that intracellular TAGE were cytotoxic in cell lines of various organs [ 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 ], our findings showed time-dependent decreases in the expression levels of LC3-II/LC3-I in cardiomyocytes treated with GA [ 37 ]. TAGE-modified proteins in cardiomyocytes have yet to be identified; however, TAGE have been suggested to alter the proteins involved in the regulation of autophagy-related pathways, such as those contributing to the generation of LC3-II.…”
Section: Cytotoxicity Of Tagecontrasting
confidence: 85%
See 2 more Smart Citations
“…The gradual accumulation of AGEs in body tissues has cytotoxic effects on tissues and cells, driving chronic diseases. 2 Recent studies have shown that methyl-glyoxal (MGO), a potent precursor for AGEs, is generated as a nonenzymatic breakdown product of a triosephosphate intermediate in the glycolytic process and has been linked to dicarbonyl stress, which leads to the development of AGEs and cellular dysfunction. 3 Amyloid fibrillation induced by excessive non-enzymatic glycation with the accumulation of AGEs is fundamental to the development of many neurodegenerative and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%